Current Status of Gil-Vernet Trigonoplasty Technique - Nasser Simforoosh; Mohammad H. Radfar (Advances in Urology)
Significant controversy exists regarding vesicoureteral reflux (VUR) management, due to lack of sufficient prospective studies. The rationale for surgical management is that VUR can cause recurrent episodes of pyelonephritis and long-term renal damage. Several surgical techniques have been introduced during the past decades. Open anti-reflux operations have high success rate, exceeding 95%, and long durability. The goal of this article is to review the Gil-Vernet trigonoplasty technique, which is a simple and highly successful technique but has not gained the attention it deserves. The mainstay of this technique is approximation of medial aspects of ureteral orifices to midline by one mattress suture. A unique advantage of Gil-Vernet trigonoplasty is its bilateral nature, which results in prevention from contralateral new reflux. Regarding not altering the normal course of the ureter in Gil-Vernet procedure, later catheterization of and retrograde access to the ureter can be performed normally. There is no report of ureterovesical junction obstruction following Gil-Vernet procedure. Gil-Vernet trigonoplasty can be performed without inserting a bladder catheter and drain on an outpatient setting. Several exclusive advantages of Gil-Vernet trigonoplasty make it necessary to reconsider the technique role in VUR management.